The Importance of the Holistic View in Urbanism: The Role of Physical Geography in the Sustainable City of the 21st Century - Cordeiro, A. M. Rochette (Advances in Social Sciences Research Journal, 2022)
The need for an interdisciplinary approach to urban planning is an undeniable fact in the 21st century vision of sustainable cities. Although in geography studies urban planning has always been regarded as a field of human geography, resilience to climate change and the importance of ecosystems in increasingly populated territories offer new perspectives to physical supports, in particular in urban design and in its relevance in environmental aspects of sustainable urban planning. This study takes an integrated approach to physical geography in order to understand urban environments through urban landscapes from a socio-natural standpoint. In the last decade, both at global level, through the Sustainable Development Goals (SDGs), and at European level, through directives and environmental programmes, such as the Urban Agenda for the EU and the European Climate Law, the adaptations of urban climate, air quality, and sustainable land-use contingent to nature-based solutions brought about new challenges and perspectives to the 21st century city. In this framework, the energy efficiency and decarbonisation issues were brought into the equation, being key elements in sustainable urban development. Adapting the sub-areas of physical geography to the different mosaics in urban spaces in a holistic manner by analysing endogenous factors – “morphological system” – and exogenous factors – climate –, as well as all those interconnected thereto downstream – hydrology, natural hazards, or the different environmental management and land-use and occupation instruments provides physical geographers with opportunities for the urbanisation of nature, in a temporal matrix, showing the trajectories of transformation of urban settlements.